2019
DOI: 10.1002/elps.201900014
|View full text |Cite
|
Sign up to set email alerts
|

Pt NPs catalyzed chemiluminescence method for Hg2+ detection based on a flow injection system

Abstract: Establishing a simple and accurate method for Hg2+ detection is of great importance for the environment and human health. In this work, platinum nanoparticles (Pt NPs) with different capped agents and morphologies were synthesized. It was found that Pt NPs exhibited peroxidase‐like activity that can catalyze the chemiluminescence (CL) of the luminol system without H2O2. The most intensive CL signals were obtained by using PVP‐capped Pt NPs as catalysis. Based on the fact that Hg2+ could further enhance the CL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…They took advantage of this catalysis mechanism and applied it toward Hg 2+ detection, as the Hg 2+ could further enhance the CL intensity in the Pt NPs-luminol CL system. With this approach, they were able to detect Hg 2+ and achieved a low-end detection limit of 8.6 nM compared with other methods (LOD ranges from 3.3 nM to 338 nM) ( Figure 8 b) [ 135 ]. Based on the intrinsic properties of Au and Pt, Wang and colleagues designed an Au@AgPt NP with surface-enhanced Raman scattering (SERS)—an active peroxidase-like activity that could be used to detect the signal molecules (which generate SERS or colorimetric signal) [ 136 ].…”
Section: Nanozymes and Their Potential Applications In Biosensingmentioning
confidence: 99%
“…They took advantage of this catalysis mechanism and applied it toward Hg 2+ detection, as the Hg 2+ could further enhance the CL intensity in the Pt NPs-luminol CL system. With this approach, they were able to detect Hg 2+ and achieved a low-end detection limit of 8.6 nM compared with other methods (LOD ranges from 3.3 nM to 338 nM) ( Figure 8 b) [ 135 ]. Based on the intrinsic properties of Au and Pt, Wang and colleagues designed an Au@AgPt NP with surface-enhanced Raman scattering (SERS)—an active peroxidase-like activity that could be used to detect the signal molecules (which generate SERS or colorimetric signal) [ 136 ].…”
Section: Nanozymes and Their Potential Applications In Biosensingmentioning
confidence: 99%
“…There are many conventional analytical techniques for detection and analysis of Hg 2+ and TU, for example, atomic absorption spectrometry, [ 23,24 ] inductively coupled plasma atomic emission spectrometry, [ 25,26 ] chemiluminescence, [ 27 ] cold vapor atomic absorption spectrometry, [ 28–30 ] fluorescence detection, [ 31 ] supramolecular polymer networks [ 32,33 ] for Hg 2+ analysis, and UV–VIS, [ 34–36 ] mass spectrometry, [ 37,38 ] Fourier‐transform infrared spectroscopy, [ 39 ] Raman spectroscopy, [ 40 ] high‐performance liquid chromatography, [ 41 ] and electrochemical methods [ 42–45 ] for TU measurements. All of the methods described above for analysis of two species have some shortcomings, for example, they need time‐consuming pretreatments, sophisticated operations, complicated detection processes, and relatively expensive instruments.…”
Section: Introductionmentioning
confidence: 99%
“…Silver and platinum nanoparticles also enhance the luminol-H 2 O 2 reaction, with a similar catalytic mechanism to Au NPs. 31,32 It was also found that the catalytic activity of silver nanoparticles (AgNPs) increased with the aggregation of small Ag NPs, due to the increase in the electron density in the Ag NPs' conduction bands. 33 Other than gold, silver and platinum, copper(II) compounds like CuFe 2 O 4 nanospheres could also act as efficient catalysts for luminol-based chemiluminescence reactions.…”
mentioning
confidence: 99%